Quality governance and performance evaluation in Malaysian public sector - Ali, Noor Azman; Mahat, Fauziah; Mukhtar, Ramlah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Quality management initiatives have been widely implemented as strategic weapons for performance improvement in many organizations including service organizations. Yet, failures have been associated with the implementations of these initiatives whereby not all quality management initiatives have given desired results in performance. Current knowledge is also limited in providing insights on the importance of quality governance (good governance of quality initiatives) as a factor for enhancing performance. This study seeks to investigate the relationships between quality practices, quality governance, and organizational performance. Survey procedures were used to sample managers involved or used to be involved in quality management initiatives in the Malaysian public service sector. A robust measurement of research construct was employed to test the hypothesized model, proving the relationships and influences on organizational performance through quality governance. The results of this study indicate that the hypothesized model attested the significance of quality governance as a factor for performance improvement through the implementation of quality initiatives. Consequently, public service organizations should be aware of the importance of having effective quality practices, especially the ones which are more customers focused, to promote quality governance in enhancing sustainable organizational performance.